ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN PADA KABUPATEN/KOTA PROVINSI BALI - Dewi Yudha, Ni Nyoman Primantika; Pramitha Purwanti, Putu Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023, 2023)
The disparity in the level of poverty between the regions of the Province of Bali indicates that welfare is still not enjoyed by the whole community. One of the efforts to reduce poverty is to increase economic growth. Economic growth is not accompanied by a reduction in inequality and an increase in other factors that support poverty reduction. The purpose of this study was to analyze the factors that influence economic growth and poverty levels in districts/cities in Bali Province. The number of observations used were 45 observation points. The data collection consisted of 9 districts/cities in Bali Province in a span of 5 years, namely 2015-2019. The collected data is then analyzed using path analysis techniques. The results of this study indicate that the level of education, working population and investment have a significant positive effect on the economic growth of districts/cities in Bali Province. The level of education, working population, investment and economic growth have a significant negative effect on the poverty level of districts/cities in Bali Province. The level of education, the working population and investment have an indirect effect on the poverty level through the economic growth of districts/cities in Bali Province